Mechanical parameters of the curvilinear squeeze film bearing lubricated by a Gecim-Winer fluid - Walicka, Anna; Walicki, Edward (Zielona Góra: Uniwersytet Zielonogórski)
Based upon a Gecim-Winer fluid flow model, a curvilinear squeeze film bearing is considered. The equations of motion are given in a specific coordinates system. After general considerations on the Gecim-Winer fluid flow these equations are used to derive the Reynolds equation. The solution of this equation is obtained by a method of successive approximation. As a result one obtains formulae expressing the pressure distribution and load-carrying capacity. The numerical examples of the Gecim-Winer fluid flow in gaps of two simple bearings: radial and spherical are presented.
Keywords: modified Reynolds equation; Gecim-Winer fluid; squeeze film; mechanical parameters of bearing; additives